THE EFFECT OF VIDEO EDUCATION ON BREASTFEEDING SELF EFFICACY IN THRID TRIMESTER PREGANT WOMEN IN THE INDEPENDENT PRATICE OF MIDWIVES IN BENGKULU CITY IN 2023 - Sherina Lumban Toruan; Nur Elly; Rahma Annisa; Mardiani Mardiani; Efrizon Efrizon (Proceeding B-ICON, 2023)
Breast milk is the most ideal food source for babies or neonate. Breast milk is easily digested by babies Breast smilk contains a mixture of various food ingredients that are right for babies. Breastfeeding Self-efficacy (BSE) is defined as a mother's confidence in her ability to breastfeed a baby. The purpose of the study was to determine "the effect of education through videos on breastfeeding self-efficacy during III trimester pregnancy. This study used an experimental method with a quasi experiment study, with a pre-post test design with control group design. The population is all 3rd trimester pregnant women who carry out ANC in BPM H and BPM S followed by children born at 3 days of age. Sampling using consecutive sampling technique. The number of respondents was 36 people consisting of 18 respondents for each intervention and control group. The intervention provided was video education while the control group was given a booklet. Data collection is done by means of Consecutive sampling. Data analysis through univariate and bivariate analysis with the Mann whitney test and T-test. The results showed that the p value of 0.012 (p value <0.05) means that there is a difference in the average value of breastfeeding self efficacy scores between groups. This shows that there is an influence of education through videos on breastfeeding self efficacy in III trimester mothers. Video education can be used as an effort to increase the confidence of mothers to provide exclusive breastfeeding.